The importance of preventing infections related to the implantation of a cardiac implantable electronic devices in the population of Bydgoszcz - Wołowiec, Łukasz; Sielski, Sławomir; Żukow, Xawery; Konieczny, Jakub; Sawicki, Przemysław; Jaśniak, Albert; Grześk, Grzegorz (Journal of Education, Health and Sport, 2023)
Cardiac implantable electronic device (CIED) infection, despite significant developments in medicine, is still a significant source of morbidity and mortality, occurring in the range of 1% to 4% of all implantation cases. A modern approach to reducing the risk of CIED infection is the use of an absorbable antibacterial coating, also known as an envelope in which the device is placed. The material from which the envelope is made is completely absorbed by the body approximately nine weeks after implantation, simultaneously releasing antibiotics. The presented manuscript discusses the importance of preventing infections related to CIEDs implantation and presents partial data on implanted CIEDs in the population of Bydgoszcz. Research into infections associated with CIED implantation is highly important as it can significantly reduce the risk of complications and improve treatment outcomes. Continued research in this field is essential to refine prevention strategies and enhance the quality of care for CIED patients. The presented data on implanted CIEDs in the population of Bydgoszcz represent a crucial step in understanding the prevalence of these devices and may provide valuable insights for further research into preventing CIED-related infections. Further analysis of this data can help develop more effective prevention strategies and improve healthcare in this area.